Enhancing Security of IoT through Quantum Cryptography - Adu-Kyere, Akwasi (fi=Turun yliopisto|en=University of Turku|, 2016)
As the role and responsibility of IoT keeps diversifying, its applicability, deployment, and communication processes needs to re-stand technological advancement. The versatile interaction between IoTs in human-to-machine and machine-to-machine communications also needs to endure cryptographic attacks that relies on mathematical and computational complexities. Security is important in IoT as the vision of autonomous ``Things" is becoming the future trend. Quantum cryptography uses the laws of quantum mechanics for generating a secure key through the manipulation of light properties to secure an end-to-end communication. An analyses on how the advantages of quantum cryptography over classic cryptography can improve IoT communications is approached from theoretical, methodological, and practical perspective. A simulation model designed with CrypTool 2 is implemented using the Python language to simulate quantum cryptographic principles ( quantum mechanics laws) with the BB84 protocol. The statistical analysis from the simulation confirms the presence of an eavesdropper is detectable in the key generation and distribution process. Due to Heisenberg's uncertainty and no-cloning principles, an eavesdropper has a probability of 0.5 chances of guessing the current quantum states and $1/4$ for the four quantum states. For this reason, an average of 50 percent bits from the total initial key is discarded through as base-mismatch process. Error detection and amplification process follows to eliminate all errors as well as strengthening the final shared key which does not match at the end when an eavesdropper is enabled during the simulation. The findings from the simulation also shows that IoT devices can get access to the final shared key through series of network configurations. The QKD nodes at the end of both communication takes care of the initial key transactions for the devices to either query directly or through sub queries. This then becomes an advantage in IoT communicational processes when coupled with classic cryptographic algorithms.